Development of multi-target dsRNAs targeting PcNLP gene family to suppress Phytophthora capsici infection in Nicotiana benthamiana - Minsu Park; Yujin Kweon; Jihyun Eom; Minsun Oh; Chanseok Shin (Applied Biological Chemistry, 2023)
Abstract Phytophthora capsici, which causes diseases in solanaceous crops, secretes necrosis and ethylene-inducing peptide 1-like proteins (NLPs) that induce plant defense responses and leaf necrosis. In this study, we used RNA interference (RNAi) technique, a proven strategy for crop protection and gene regulation in plants, to suppress P. capsici infection through the inhibition of PcNLPs. In the RNAi mechanism, Dicer processes double-stranded RNA (dsRNA) into smaller entities known as small interfering RNAs (siRNAs). These siRNAs subsequently integrate into the RNA-induced silencing complex to form sequence-specific base pairing with complementary regions of the target mRNA. This interaction effectively initiates the degradation process of the target mRNA. We designed and synthesized dsRNAs targeting the “AIMY” and “GHRHDWE” conserved motifs of PcNLP gene family, which are predicted to be key elements for the expression of NLPs and pathogen infection. After infiltration of dsRNAs targeting the motifs and inoculation with P. capsici, we confirmed a significant suppression of P. capsici infection and downregulation of the PcNLP gene family. These findings imply that the dsRNA-mediated RNAi technique holds potential for mitigating a wide range of pathogens, while simultaneously suppressing the expression of a particular gene family using dsRNA targeting functional conserved motifs in the gene family.